Differences in Lactate Dehydrogenase (LDH) Levels in Packed Red Cells (PRC) with Various Storage Times - Ersanto, Novi; Harmoko, Deni; Lukiyono, Yauwan Tobing (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2025)
This research seeks to analyze the storage duration effect on PRC (Packed Red Cell) quality by assessing changes in LDH (Lactate Dehydrogenase) levels on storage days 1, 10, 20, and 30. This research is an observational analytical study with a time series design. The research was conducted at the Blood Transfusion Installation of Dr. Soetomo General Hospital Surabaya as the sampling site and the Clinical Laboratory of the Faculty of Health Sciences, Maarif Hasyim Latif University, Sidoarjo as the place for measuring research variables. The research sample consisted of fifty PRC bags from voluntary donors. LDH levels were examined with a Semi-Automatic Chemistry Analyzer Sinnowa BS-3000P Photometer (Sinnowa Medical Science & Technology Co., Ltd., China) and measured on days 1, 10, 20, and 30. The research data were analyzed using SPSS 25 statistical software. Data normality was analyzed using the Shapiro-Wilk test. Comparison of PRC quality was analyzed using repeated measure ANOVA analysis (same object analysis) if the data were normally distributed, or the Freedman test if the data distribution was not normal. The findings revealed that there was an increase in mean LDH levels with increasing PRC storage duration over 30 days. Repeated Measure ANOVA test and the Post Hoc Bonferroni test for LDH levels showed that there were statistically significant differences with a significance value of p < 0.001 at all observation times. In conclusion, there are significant differences in LDH levels during Packed Red Cell (PRC) storage from day 1, day 10, day 20, and day 30.